Study on the hydrogen storage properties of a TiZrNbTa high entropy alloy. (14th February 2020) - Zhang, Cheng; Song, Anna; Yuan, Yuan; Wu, Yuan; Zhang, Peilong; Lu, Zhaoping; Song, Xiping
Abstract: High-entropy alloys (HEAs), as a new class of metallic materials, have received more and more attention due to its excellent mechanical properties. In this study, the hydrogen absorption properties, such as hydrogen absorption capacity, thermodynamics, kinetics and cyclic properties, as well as the hydride structure of a newly designed TiZrNbTa HEA were investigated. The results showed that multiple hydrides including ε-ZrH2, ε-TiH2 and β-(Nb, Ta)H were found in the TiZrNbTa HEA after hydrogenation. With the increase of temperature from 293 K to 493 K, the maximum hydrogen absorption capacity decreased from 1.67 wt% to 1.25 wt% and the plateau pressure related with β-(Nb, Ta)H hydrides increased from 1.6 kPa to 14.8 kPa. The formation enthalpy of β-(Nb, Ta)H hydride was determined to be −6.4 kJ/mol, which was less stable than that of NbH and TaH hydrides. The results also showed that the TiZrNbTa HEA exhibited a rapid hydrogen absorption kinetic even at the room temperature with a short incubation time, and the hydrogen absorption mechanism was determined to be the nucleation and growth mechanism. Moreover, the hydrogen absorption capacity at 293 K decreased slowly with the cycle numbers, and remained 86% capacity after 10 cycles. Cracking occurred after hydrogen absorption and became worse with cycles. Highlights: Multiple hydrides are observed in the TiZrNbTa high entropy alloy after hydrogenation. The maximum hydrogen absorption capacity decreases and the plateau pressure increases with the temperature. The TiZrNbTa exhibits an excellent hydrogen absorption kinetic characteristics even at room temperature. The hydrogen absorption capacity of TiZrNbTa decreases slowly with the cycle numbers.